2016
DOI: 10.1016/j.cortex.2015.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Rhythm makes the world go round: An MEG-TMS study on the role of right TPJ theta oscillations in embodied perspective taking

Abstract: While some aspects of social processing are shared between humans and other species, some aspects are not. The former seems to apply to merely tracking another's visual perspective in the world (i.e., what a conspecific can or cannot perceive), while the latter applies to perspective taking in form of mentally "embodying" another's viewpoint. Our previous behavioural research had indicated that only perspective taking, but not tracking, relies on simulating a body schema rotation into another's viewpoint. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
144
2

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 83 publications
(168 citation statements)
references
References 59 publications
22
144
2
Order By: Relevance
“…For the right TPJ, we identified a specific effect of inhibiting the self--perspective during allocentric perspective taking with a greater reliance on embodied mental rotation. Our results provide support for the theory that the rTPJ has a causal role in inhibiting the egocentric perspective during embodied rotation (Wang et al, 2015). As we did not identify a general effect of reducing congruency effects for both self and other processing, our results do not support the theory that rTPJ has a non--specific effect for self--other distinction (Santiesteban et al, 2012).…”
Section: Discussioncontrasting
confidence: 85%
See 3 more Smart Citations
“…For the right TPJ, we identified a specific effect of inhibiting the self--perspective during allocentric perspective taking with a greater reliance on embodied mental rotation. Our results provide support for the theory that the rTPJ has a causal role in inhibiting the egocentric perspective during embodied rotation (Wang et al, 2015). As we did not identify a general effect of reducing congruency effects for both self and other processing, our results do not support the theory that rTPJ has a non--specific effect for self--other distinction (Santiesteban et al, 2012).…”
Section: Discussioncontrasting
confidence: 85%
“…A meta--analysis of self--referential processes using fMRI identified the dmPFC as the key region for other--related processes with less evidence for TPJ involvement (Denny, Kober, Wager, & Ochsner, 2012). This would suggest that the rTPJ is not involved in domain general processing of other--related representations and more has a role in either online control (Santiesteban et al, 2012), inhibition of the self or egocentric bias (Payne & Tsakiris, 2017;Soutschek et al, 2016), or embodied rotation (Wang, Callaghan, Gooding--Williams, McAllister, & Kessler, 2015). In a previous study, we identified a polarity specific (anodal v cathodal) modulation of dmPFC function when integrating other representations into self--representations across VPT and episodic memory domains (Martin, Dzafic, Ramdave, & Meinzer, 2017).…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…In general the temporal integration windows required for optimal decoding of a social interaction are likely to increase with the complexity of the interaction, requiring ever finer coordination between low frequencies across cortical areas with local high frequency gamma (conforming to Arnal & Giraud, 2012). Recently, the relevance of theta-based networks for high-level social cognition (perspective taking, mentalizing) has indeed been reported (Bögels et al, 2014;Wang et al, 2016), and requires further investigation with ASD participants and finer-grained analysis of local phase and cross-frequency coupling. We hypothesise (Table 4, Hypothesis 8) that low frequency (delta-theta) cross-cortical phase coupling should be affected in ASD in conjunction with reduced local PAC and possibly inter-trial phase coherence during highlevel social cognition.…”
Section: Explaining Asd Symptomatology Beyond Sensory Aberrationsmentioning
confidence: 99%